Investigation of Volatile Organic Compounds of Whole-Plant Corn Silage Using HS-SPME-GC-MS, HS-GC-IMS and E-Nose - Yinge Chen; Lulu Wang; Yawei Zhang; Nan Zheng; Yuanqing Zhang; Yangdong Zhang (Agriculture)
To investigate the source of the bitter almond taste in whole corn silage (WPCS), headspace solid-phase microextraction combined with gas chromatography–mass spectrometry (HS-SPME-GC-MS), headspace gas chromatography–ion migration spectrometry (HS-GC-IMS), and electronic nose (E-nose) technology were employed. The study analyzed the differences in volatile compounds between two WPCS samples with distinct odors from the same cellar. GC-IMS and GC-MS identified 32 and 101 volatile organic compounds (VOCs), respectively, including aldehydes, alcohols, esters, ketones, and other compounds. Three characteristic volatile organic compounds associated with the bitter almond taste were detected: benzaldehyde, cyanide, and isocyanate. The electronic nose demonstrated varying sensitivities across its sensors, and principal component analysis (PCA) combined with variable importance projection (VIP) analysis revealed that W5S (nitrogen oxides) could differentiate between the two distinct silage odors. This finding was consistent with the GC-MS results, which identified 34 nitrogen-containing heterocyclic compounds in the abnormal silage sample, accounting for 77% of the total nitrogen-containing compounds. In summary, significant differences in aroma composition were observed between the bitter almond-flavored silage and the other silage in the same cellar. These differences were primarily attributed to changes in volatile organic compounds, which could serve as indicators for identifying bitter almond-flavored silage.